Reading Questions in English Textbook Based on Bloom’s Taxonomy - Roy Indra Pratama Situmorang and Anggraini T. Saragih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study aimed at analyzing the cognitive domain of Bloom’s Taxonomy already appropriate to fulfil of reading questions in the contextual teaching and learning (fourth edition) textbook for ninth grade or not. It was conducted by using descriptive qualitative design. The data were analyzed by using Table analysis of cognitive domain of Bloom’s Taxonomy. The findings showed that cognitive domain in Bloom’s Taxonomy already appropriate to fulfil reading questions in the textbook. It was proven by the data there were: Remembering obtains 73 of 145 reading questions or 50.3%, Understanding obtains 29 of 145 reading questions or 20%, Applying obtains 10 of 145 reading question or 6.9%, Analyzing obtains 19 of 145 reading questions or 13.1%, Evaluating 6 of 145 reading questions or 4.1% and Creating 8 of 145 reading questions or 5.6%. These results do not achieve the regulation by ministry of education and culture who said for Junior High School itself the proportion is remembering - understanding 20%, applying-analyzing 55%, evaluating 15%, and creating 10%.